2022
DOI: 10.3389/fpls.2022.1050132
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of ABA and ROS in plant growth and stress resistances

Abstract: The plant hormone ABA (abscisic acid) plays an extremely important role in plant growth and adaptive stress, including but are not limited to seed germination, stomatal closure, pathogen infection, drought and cold stresses. Reactive oxygen species (ROS) are response molecules widely produced by plant cells under biotic and abiotic stress conditions. The production of apoplast ROS is induced and regulated by ABA, and participates in the ABA signaling pathway and its regulated plant immune system. In this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 207 publications
(281 reference statements)
1
18
0
Order By: Relevance
“…The strength of free radical scavenging or antioxidant capacity in plants can be reflected in their activity levels, serving as indicators of plant stress resistance. 48 Our study revealed that AZOX-AFS-Pec NPs could enhance the SOD and POD activities in rice plants, indicating that AZOX-AFS-Pec NPs could activate defense responses in rice plants against pathogenic invasion. Additionally, changes in protective substances in plants' postpathogenic infection closely correlated with their disease resistance.…”
Section: Amount Of Iron Ionmentioning
confidence: 59%
“…The strength of free radical scavenging or antioxidant capacity in plants can be reflected in their activity levels, serving as indicators of plant stress resistance. 48 Our study revealed that AZOX-AFS-Pec NPs could enhance the SOD and POD activities in rice plants, indicating that AZOX-AFS-Pec NPs could activate defense responses in rice plants against pathogenic invasion. Additionally, changes in protective substances in plants' postpathogenic infection closely correlated with their disease resistance.…”
Section: Amount Of Iron Ionmentioning
confidence: 59%
“…At this point it is worth mentioning that we have previously demonstrated that AtSBP1 is highly expressed in the guard cells of the stomata [ 13 ]. Moreover, ABA and ROS cross-talking is also observed during biotic and abiotic stress, as well in plant development and growth [ 43 ]. Another study focused on rice revealed that ABA produced during heat stress prevents the reduction of pollen viability and spikelet fertility [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…One physiological response associated with ABA is the production of Reactive Oxygen Species (ROS), in particular H 2 O 2 , a signalling molecule that regulates plant stress response genes (Li et al, 2022). To further confirm such an association, the H 2 O 2 content was determined in detached leaves of the four Arabidopsis mutants and Col-0 plants after 24 h of mite infestation (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Vos et al ., (2013) also reported that ABA is a crucial regulator of induced resistance against Pieris rapae by activating primed JA-regulated defence responses in Arabidopsis. Additionally, ABA has also been associated with redox homeostasis (Li et al, 2022), in particular with ROS accumulation, which is also essential in the plant defence against mites (Santamaría et al, 2017; Arnaiz et al, 2021). Our results showed increased levels of JA signalling and H 2 O 2 production in ABA deficient mutants after mite infestation where leaf damage was increased.…”
Section: Discussionmentioning
confidence: 99%